The Effect of Green Tea Leaf Extract on Spatial Memory Function and Superoxyde Dismutase Enzyme Activity in Mice with D-galactose Induced Dimentia - Gumay, Ainun Rahmasari; Bakri, Saekhol; Utomo, Astika Widy (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2017)
Background: Oxidative stress and inflammation play an important role in pathogenesis of brain aging and neurodegenerative diseases such as Alzheimer. Green tea has been shown to have antioxidant, anti-inflammatory, anticancer, and neuroprotective activity.Objectives: to determine the effect of green tea extract on spatial memory function and superoxide dismutase enzyme activity in mice with D-galactose induced dementiaMethods: An experimental study using "post test only control group design". Twenty male BALB/c Mice aged 6-8 weeks were divided into 4 groups. Negative control group (NG) was induced by subcutaneous injection of D-galactose (150 mg/kg BW) once daily for 6 weeks. GT-90, GT-270, GT-540 were induced by D-galactose and orally administered with 90, 270, and 540 mg/kg BW of green tea extract once daily for 6 weeks. The spatial memory functions were assessed using Morris water maze and SOD enzyme activities were evaluated using ELISA. One-way Anova and Kruskal-Wallis were used for statistical analysis. Results: mean percentage of latency time in the GT-90 (35.29 (SD= 2.69)%), GT-270 (35.28 (SD= 2.62)%), and GT-540 (35.62 (SD=5.05)%) were significantly higher compared to that of NG (20.38 (SD = 3.21)%), p <0.05). SOD enzyme activity in the GT-270 (0.78 (SD = 0.07) U/ml) was significantly higher compared to that of NG (0.51 (SD = 0.01) U ml), p= 0.004).Conclusion: Green tea extract may improve spatial memory function and the activity of superoxide dismutase enzyme in mice with D-galactose induced dementia.